Pengaruh Jam Kerja dan Tenaga Kerja terhadap Upah Kerja dengan Loyalitas Sebagai Variabel Intervening : (Studi Kasus Penjahit Konveksi di Kota Medan) - Muhammad Yusril; Sri Ramadhani; Nuri Aslami (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of working hours and labor on wages with loyalty as an intervening variable (Case Study of Convection Tailors in Medan City). The research method used is a survey method by distributing questionnaires to respondents consisting of several convections in Medan City. This research uses quantitative methods, primary data collection techniques by distributing questionnaires. The population and sample were 85 respondents and used a saturated total sampling technique. This research uses SPSS statistical tools. The data was analyzed using multiple regression analysis methods. The results of this study indicate that Working Hours have a significant effect on Wages. This is evidenced by because the tcount for the Working Hours variable (2.314) is greater than the ttable (1.989) and the sig value is 0.014 <0.05. Labor has a significant effect on wages. This is evidenced by because the tcount for the Labor variable (3.609) is greater than the ttable (1.989) and the sig value is 0.001 <0.05. Loyalty cannot mediate the effect of working hours on wages. This is evidenced by because the tcount for the indirect effect of the Working Hours variable (0.007) is smaller than the ttable (1.989). Loyalty can mediate the effect of Labor on Wages. This is evidenced by because the tcount for the indirect effect of the Working Hours variable (2.025) is greater than the ttable (1.989). As well as Working Hours and Labor have a simultaneous and significant effect on Wages. This is evidenced by because the Fcount of (6.518) is greater than the Ftable (3.11) and the sig value of 0.002 <0.05.